IMPLEMENTASI KEBIJAKAN JAMINAN KESEHATAN NASIONAL DI KABUPATEN BANDUNG - Eko Bayu Nugroho; Widya Setiabudhi; Mohammad Benny Alexandri (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Background The Bandung Regency Government has implemented the National Health Insurance (JKN) program as mandated by Presidential Regulation Number 82 of 2018. JKN participation in Bandung Regency is still below the 95% target and budget utilization is not optimal. This study is expected to provide recommendations for achieving UHC in Bandung Regency. Research Objectives: In Bandung Regency, to find out the substance and context of the implementation of the JKN policy to find out the reasons and suggestions that limit the implementation of UHC. Methods: This type of research is qualitative, descriptive and the Bandung Regency Health Insurance Satlak Team is the research site in Bandung Regency. The research tool is an in-depth guide to interviews. Content and JKN policies are implemented in Bandung Regency. The research variable is content. Results: In terms of substance and context of policy implementation, the JKN policy in Bandung Regency has been implemented well. However, there are still obstacles in recording the population, so that the UDB data at the Kelurahan level has not been updated optimally. Conclusion: understanding the substance and context of the JKN policy implemented by Bandung Regency to fulfill the basic rights of the community in health services. Updating the UDB data affects the accuracy and availability of funds to ensure that JKN covers the community.